A novel scheme for the validation of an automated classification method for epileptic spikes by comparison with multiple observers. Issue 7 (July 2017) - Sharma, Niraj K.; Pedreira, Carlos; Centeno, Maria; Chaudhary, Umair J.; Wehner, Tim; França, Lucas G.S.; Yadee, Tinonkorn; Murta, Teresa; Leite, Marco; Vos, Sjoerd B.; Ourselin, Sebastien; Diehl, Beate; et al.
Highlights: We created a validation method for the evaluation of automated classification of interictal spikes. We used a modified version of Wave_clus (WC) to automatically classify the data of 5 patients. WC classification was similar to EEG reviewers providing an unbiased evaluation of the clinical data. Abstract: Objective: To validate the application of an automated neuronal spike classification algorithm, Wave_clus (WC), on interictal epileptiform discharges (IED) obtained from human intracranial EEG (icEEG) data. Method: Five 10-min segments of icEEG recorded in 5 patients were used. WC and three expert EEG reviewers independently classified one hundred IED events into IED classes or non-IEDs. First, we determined whether WC-human agreement variability falls within inter-reviewer agreement variability by calculating the variation of information for each classifier pair and quantifying the overlap between all WC-reviewer and all reviewer-reviewer pairs. Second, we compared WC and EEG reviewers' spike identification and individual spike class labels visually and quantitatively. Results: The overlap between all WC-human pairs and all human pairs was >80% for 3/5 patients and >58% for the other 2 patients demonstrating WC falling within inter-human variation. The average sensitivity of spike marking for WC was 91% and >87% for all three EEG reviewers. Finally, there was a strong visual and quantitative similarity between WC and EEG reviewers. Conclusions: WC performance is indistinguishable to that of EEG reviewers' suggesting it could be a valid clinical tool for the assessment of IEDs. Significance: WC can be used to provide quantitative analysis of epileptic spikes.